2008
DOI: 10.1016/j.abb.2008.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional diversity of ferredoxin-NADP+ reductases

Abstract: Although all ferredoxin-NADP+ reductases (FNRs) catalyze the same reaction. i. e. the transfer of reducing equivalents between NADP(H) and ferredoxin, they belong to two unrelated families of proteins: the plant type and the glutathione reductase type of FNRs. Aim of this review is to provide a general classification scheme for these enzymes, to be used as a framework for the comparison of their properties.Furthermore, we report on some recent findings, which significantly increased the understanding of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
145
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 79 publications
1
145
0
Order By: Relevance
“…Because FNRs have multiple phylogenetic origins, comparative studies of different FNR group enzymes with respect to the mechanisms regulating substrate binding and catalytic properties are necessary for a deeper understanding of the structure-function relationships of FNR. With monomeric FNRs of the plastid-type and the mitochondria-type, substrate binding and reaction mechanisms have been extensively studied [for reviews, see 6,7,10,21]. However, few such studies have been reported on the proteobacteria-type [14,15] and no such studies have been reported on the Firmicutes and green sulfur bacteria-type FNRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because FNRs have multiple phylogenetic origins, comparative studies of different FNR group enzymes with respect to the mechanisms regulating substrate binding and catalytic properties are necessary for a deeper understanding of the structure-function relationships of FNR. With monomeric FNRs of the plastid-type and the mitochondria-type, substrate binding and reaction mechanisms have been extensively studied [for reviews, see 6,7,10,21]. However, few such studies have been reported on the proteobacteria-type [14,15] and no such studies have been reported on the Firmicutes and green sulfur bacteria-type FNRs.…”
Section: Introductionmentioning
confidence: 99%
“…This architecture is typical of the NAD(P) + /NAD(P)H-linked flavoenzyme family including disulfide reductases such as glutathione reductase and thioredoxin reductase [5][6][7]20]. Because FNRs have multiple phylogenetic origins, comparative studies of different FNR group enzymes with respect to the mechanisms regulating substrate binding and catalytic properties are necessary for a deeper understanding of the structure-function relationships of FNR.…”
Section: Introductionmentioning
confidence: 99%
“…+ oxidoreductase ([EC 1.18.1.2], [EC 1.18.1.3], FNR) is a member of the dehydrogenase family of the flavoprotein superfamily (Aliverti et al, 2008;Dym and Eisenberg, 2001;Correll et al, 1993). FNR catalyzes the redox reaction between the two electron carrier nucleotides, NAD(P)H, and the one electron carrier iron-sulfur proteins, ferredoxin (Fd), adrenodoxin (Ad) and putidaredoxin (Pd), and also the low molecular weight flavoprotein, flavodoxin.…”
Section: Ferredoxin-nad(p)mentioning
confidence: 99%
“…Fd is ubiquitous in almost all organisms, functioning as an electron mediator in cytochrome P450 dependent hydroxylation, nitrogen assimilation, and NADP + reduction from reduced Fd during photosynthesis (Aliverti et al 2008;Ceccarelli et al 2004;Munro et al 2007; Knaff and Hirasawa 1991;Ewen et al 2011). FNR, a member of the flavoprotein superfamily, contains a flavin adenine dinucleotide (FAD) or rarely, FMN as the prosthetic group.…”
Section: Introductionmentioning
confidence: 99%
“…FNRs are structurally and phylogenetically classified into two unrelated families including five subgroups (Aliverti et al 2008;Dym and Eisenberg 2001;Correll et al 1993;Karplus and Faber 2004;Seo et al 2004;Muraki et al 2010). Phylogenetic analyses of the deduced amino acid sequences (Seo et al 2004) and crystal structures of FNRs from the green sulfur bacterium Chlorobaculum tepidum (Muraki et al 2010), the low GC gram positive bacterium Bacillus subtilis (BsFNR, Komori et al 2010) and thermophile Thermus thermophiles (PDB code; 2ZBW) have revealed that these FNRs are homologous to the NADPH-dependent bacterial thioredoxin reductase (TrxR) from Escherichia coli (EcTrxR) (Waksman et al 1994), referred as a TrxR-type FNR.…”
Section: Introductionmentioning
confidence: 99%